Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M209 - Hoving, Henk-Jan T; Greinert, Jens; Keller, Mareike; Stauffer, Julian B; Mohrmann, Jochen; Wölfl, Anne-Cathrin; Schumacher, Mia (PANGAEA, 2025)
Raw multibeam bathymetry data were collected aboard RV METEOR during cruise M209 using a Kongsberg EM 122 multibeam echosounder. The expedition took place during 21.03.2025 - 23.04.2025 from Mindelo (Cabo Verde) - Ponta Delgada (Azores) in the North Atlantic. The cruise M209 aimed to better understand the deep-sea ecosystems in the vicinity of the Cape Verde islands. During the expedition, we applied established and novel mapping, in situ observational and sampling tools, and processed the collected samples to prepare them for genomic and other analytic approaches for our biodiversity and foodweb studies. By performing a standardized research program at the islands Santo Antão, Fogo and Santiago we will be able to compare the biological, bathymetric and physical characteristics of deep-sea habitats within the Cape Verde archipelago, with the ultimate goal to generate data to serve conservation efforts. Data were recorded within the EEZs of Cape Verde. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research, provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam Echosounder